2009
DOI: 10.1007/s11606-009-0929-5
|View full text |Cite
|
Sign up to set email alerts
|

Tea Consumption and Risk of Type 2 Diabetes: A Meta-Analysis of Cohort Studies

Abstract: BACKGROUND: Tea consumption has been extensively studied in relation to various diseases, several epidemiologic studies have been performed to investigate the association of tea consumption with type 2 diabetes; however, the results of these studies were not entirely consistent. OBJECTIVE:To conduct a meta-analysis of studies that assessed the association of tea consumption and the risk of type 2 diabetes. RESEARCH DESIGN AND METHODS:We performed a systematic literature search through November 2008 in PUBMED, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 55 publications
4
69
2
1
Order By: Relevance
“…Another study found an association only for green tea, not for black or oolong tea [6]. A recent meta-analysis summarised these studies and concluded that consumption of at least four cups of tea may lower the risk of type 2 diabetes, but a reduced risk was not observed for one to three cups of tea per day [33]. In addition, they were unable to distinguish between black and green tea in this meta-analysis.…”
Section: Discussionmentioning
confidence: 78%
“…Another study found an association only for green tea, not for black or oolong tea [6]. A recent meta-analysis summarised these studies and concluded that consumption of at least four cups of tea may lower the risk of type 2 diabetes, but a reduced risk was not observed for one to three cups of tea per day [33]. In addition, they were unable to distinguish between black and green tea in this meta-analysis.…”
Section: Discussionmentioning
confidence: 78%
“…Because tea is the most widely consumed beverage worldwide (Higdon and Frei, 2003), and because numerous epidemiological studies have suggested tea may have a role in reducing risk of diabetes (Greenberg et al, 2005;Song et al, 2005;Iso et al, 2006;Odegaard et al, 2008;Polychronopoulos et al, 2008;Jing et al, 2009;van Dieren et al, 2009), controlled intervention studies are important for defining the potential for tea to maintain healthy glucose metabolism. Oolong tea processing involves fermenting the product more than green tea is fermented, but less than black tea.…”
Section: Discussionmentioning
confidence: 99%
“…As little as one cup of black tea per day was associated with decreased risk of diabetes in a study of 36 908 men and women in the Singapore Chinese Health Study (Odegaard et al, 2008). Jing et al (2009) conducted a meta-analysis that considered many of these studies together and concluded that tea consumption of four or more cups per day 'might have a role in prevention of type 2 diabetes.' In contrast, a number of large survey studies do not support a relationship between tea intake and diabetes risk, including the Health Professionals' Follow-up Study (Salazar-Martinez et al, 2004), the Nurses' Health Study (Salazar-Martinez et al, 2004) and the Nurses' Health Study II (van Dam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…46 The role of tea (all types included) in the prevention of type 2 diabetes mellitus development has been highlighted in two recent meta-analyses, where consumption of more than 3 to 4 cups per day of tea of any type was associated with reduced subsequent incidence of type 2 diabetes mellitus. 47,48 Green tea acutely increases glucose metabolism and improves oral glucose tolerance test in healthy humans. 49 However, these beneficial effects have not been verified in intervention studies of short-to middle-term green tea consumption.…”
Section: Glucose Metabolismmentioning
confidence: 99%